Quality of Bread and Cookie Baked from Frozen Dough and Batter Containing β‐Glucan‐Rich Barley Flour Fraction. Issue 5 (29th July 2015) - Hamed, Abdelmagid; Ragaee, Sanaa; Marcone, Massimo; Abdel‐Aal, El‐Sayed M.
Abstract Prolonged frozen storage of dough and batter unfavorably affects the quality of end baked products. The effect of air‐classified barley flour fraction rich in β‐glucan (∼25%) on the quality of bread and cookie baked from frozen dough/batter was investigated. Dough and batter were stored at −18C for 8 and 4 weeks, respectively, and evaluated for baking quality at weekly intervals. Bread made from fresh control dough produced the highest loaf specific volume (LSV) compared with those baked from composite dough. Control and composite frozen dough breads exhibited similar LSV and crumb texture profile up to 4 weeks of storage. Frozen storage of batter for 4 weeks resulted in no significant changes in either hardness or stickiness of batter and spread factor of cookie compared with control, while breaking force of cookie decreased. The addition of β‐glucan‐rich barley flour fraction holds a promise for developing fiber‐rich bread or cookie from frozen dough or batter. Practical Applications Incorporation of air‐classified barley flour fraction rich in β‐glucan in bread dough and cookie batter stored at freezing temperature (−18C) improves their shelf life through the restriction of water mobility in dough or batter without compromising the quality of baked end products. Such data can be invaluable in the baking industry.